Językowa kreacja nieba i piekła w Tragedii o bogaczu i Łazarzu z 1643 roku - Kępka, Izabela (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The main goal of the article is showing the language creation of hell and heaven presented in The tragedy about the rich man and Lazarus in XVII c. Language creation of hell and heaven in this story is showing it stereotypically. Heaven is a place where God and other peaceful creatures live (also souls of people that lived well on Earth). Hell is a dark abyss, where the fire of hell (which is not shining) is the main source of pain for the condemned. A human being which got into hell will never get out. It is out of God’s forgiveness range. The image of those two places in the Tragedy serves mainly the persuasion which is closely connected with the genre of the morality. Language creation of hell and heaven in the Tragedy was written by uncomplicated linguistic means.